Pembuatan Ecobrick sebagai Upaya Menumbuhkan Sekolah Ramah Lingkungan di SMP PGRI 30 Jakarta dalam Rangka Mendukung Program Sekolah Adiwiyata - Fadjriah Hapsari; Siti Wahyuni (LITERATUS, 2020)
The increasing amount of plastic waste in community consumption activities both in the household and in school is a never ending study. As we know, school is a cultural center for civilization, so plastic waste is also major concern for school. In terms of plastic waste, school has also contributed to the increase, because there is still a lot of plastic use in the school environment. Ecobricks are a method that schools can apply in overcoming waste problems. This research discusses the making of ecobricks in realizing environmentally friendly schools to support Adiwiyata school programs. The method used in this research is descriptive methode to reveal the real facts. After the practice is carried out an evaluation is carried out. The results obtained from this study can be seen from : 1). Students have been able to practice making ecobricks by utilizing plastic waste and plastic bottle waste. 2). Students are able to create ecobricks into attractive decorations in the school environment. 3). Students are able to motivate themselves in making ecobricks. 4). Students show high interest and enthusiasm in making ecobricks. 5). Students are able to use ecobricks to become a school garden fence. 6). This ecobricks is a simple solution in processing plastic waste to be useful.